Fotointerpretacao comparativa de fotografias pancromaticas, imagens de radar e de satelite - Garcia, G. J.; Norton, L. D.; Espindola, C. R. (My University, 1981)
Three types of imagery were evaluated for mapping drainage patterns and vegetation in a 100 000 ha area of Sao Paulo State, Brazil. The drainage measurements were drainage density, frequency of channels and texture ratio, studied on circular samples of 10 km2 for panchromatic photography and 100 km2 for radar and satellite images. The vegetation types were forest, pasture, sugar cane and rice, studied on circular samples of 100 km2. Radar images were the most convenient method to study drainage patterns and the land forms of large areas, while Landsat imagery was most efficient for the study of vegetative cover, although panchromatic photographs were the most accurate method.-from Field Crop Abstracts
Comparative photointerpretation of panchromatic photographs, radar and satellite images